Are our further education colleges still an anchor in our society?. (8th March 2023) - Senior, Lynn; Barnes, Neil
Abstract : This article reviews the impact of further education (FE) colleges – in particular, mixed economy colleges – on the surrounding environment and community, and attempts to answer the question of whether the mixed economy college can still be considered an anchor in the community. A mixed methods small-scale case study of a medium-sized mixed economy college was used to evaluate a range of issues that impact on the local community, considering the future and expansion of 16–19 education, against the backdrop of decreases in college provision in the East of England. The aim was to present the background and brief history of the mixed economy college's impact on the surrounding community, particularly through associated financial, economic and environmental measurements. In conclusion, the authors argue that FE/mixed economy colleges can add significant value to the surrounding environment, community and wider society, and that they are still an anchor in the environment and local communities in which they are situated. They further posit that the goal is for all involved in the FE/mixed economy community to contribute to the shared aim of widening access to lifelong learning, thus further improving the communities and environment in which students and staff reside and work.